2007
DOI: 10.1258/004947507781524719
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic variceal sclerotherapy in patients with Symmers periportal fibroses

Abstract: This is a prospective study, carried out in patients with portal hypertension and bleeding oesophageal varices secondary to Symmers (Schistosomal) periportal fibroses, to determine the efficacy of sclerotherapy, the number of sessions needed to achieve full sclerosis, the complications associated with sclerotherapy and the incidence and risk factors for rebleeding. In total, 85 patients were studied with a mean age of 38 years, 76.5% were males. All underwent upper gastrointestinal endoscopy, had different gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Significant factors contributing to the 6-wk rebleeding rate in PPF group were grade III PPF on abdominal ultrasound and blood transfusion on admission ( P value < 0.004 and < 0.02 respectively). A previous study from Sudan demonstrated that rebleeding was more in grade III PPF[17]. A study from Brazil also found that the sonographic grade of periportal fibrosis was an important tool in predicting variceal complications in patients with schistosomal PPF[18], whereas the longitudinal spleen dimension of more than 11 cm, was an important tool in predicting variceal bleeding in another study[6].…”
Section: Discussionmentioning
confidence: 99%
“…Significant factors contributing to the 6-wk rebleeding rate in PPF group were grade III PPF on abdominal ultrasound and blood transfusion on admission ( P value < 0.004 and < 0.02 respectively). A previous study from Sudan demonstrated that rebleeding was more in grade III PPF[17]. A study from Brazil also found that the sonographic grade of periportal fibrosis was an important tool in predicting variceal complications in patients with schistosomal PPF[18], whereas the longitudinal spleen dimension of more than 11 cm, was an important tool in predicting variceal bleeding in another study[6].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 30% of bleeding episodes are fatal, while in this study it was seen in 6% of patients after receiving treatment in the form of pharmacotherapy and endoscopic treatment, which is comparable to Mudawi study (3.5%). (38) In this study it was found that most of the patients were farmers (80%) and living nearby the Blue Nile and its irrigating canal system. According to WMTH statistics, in the last eight years the total number of patients with oesophageal varices were 1140 and 947 of them were from Gezira state accounting for 83% of patients, which is an endemic area for schistosomiasis.…”
Section: Discussion:-mentioning
confidence: 71%
“…The recurrence rate in this study was 17 patients (22.6%), while it was seen in 32% in Mudawi`s study. (38) Conclusions & Recommendations:-Conclusions:- The main presentation of bleeding oesophageal varices is haematemesis, however it can present with melaena.  Pancytopenia and splenomegaly are highly associated with bleeding oesophageal varices.…”
mentioning
confidence: 99%
“…Also, endoscopic therapy has poorer long-term results although it's less invasive than surgery [126,127] . Furthermore, in 2007 Mudawi and Ibrahim [128] found high rates of variceal rebleeding in 32% of patients with schistosomiasis treated by endoscopic sclerotherapy for secondary prophylaxis and mortality rate was three and a half percent.…”
Section: Surgical Treatments Of Refractory Variceal Bleedingmentioning
confidence: 99%